Respuesta :
ANSWER
[tex]B(2,-3)[/tex]
[tex]C(-2,3)[/tex]
EXPLANATION
The given point has coordinates A(-2,-3).
The rule for the reflection across the y-axis is
[tex](x,y)\to(-x,y)[/tex]
We apply this rule to obtain the coordinates of B.
[tex]A(-2,-3)\to B(--2,-3)[/tex]
Simplify the coordinates of B to get:
[tex]A(-2,-3)\to B(2,-3)[/tex]
The rule for reflection across the x-axis is
[tex](x,y)\to (x,-y)[/tex]
When the point A(-2,-3) is reflected across the x-axis to obtain C, then the coordinates of C are:
[tex]A(-2,-3)\to C(-2,--3)[/tex]
[tex]A(-2,-3)\to C(-2,3)[/tex]
Answer:
B(2 ,-3) and C( -2, 3)
Step-by-step explanation:
i did the test lol :)